“Elaboración de bebida instantánea y manjar en base de fréjoles huasca poroto ( phaseolus vulgaris) y caupi ( vigna unguiculata)” - Chávez Salazar,Angel (1992)
The present work is the formulation and evaluation of mathematics of twenty alternatives based on two varieties of bean mixes; huasca bean (phaseolus vulgaris), Cowpea (vigna unquiculata), sapino(mussa spp.) banana, milk powder, wheat flour and sugar, by selecting the formulation of 477.5% bean, 4.5% milk powder, 14.5% wheat flour, 9% banana sapino and 24.5% based on bean huasca bean and 50 sugar % bean, milk powder, 4% 14% wheat flour, 8% banana, 24% sugar based on Cowpea beans.